2013
DOI: 10.1107/s0909049513021298
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the human-heart fatty-acid-binding protein 3 in complex with the fluorescent probe 1-anilinonaphthalene-8-sulphonic acid

Abstract: Heart-type fatty-acid-binding protein (FABP3), which is a cytosolic protein abundantly found in cardiomyocytes, plays a role in trafficking fatty acids throughout cellular compartments by reversibly binding intracellular fatty acids with relatively high affinity. The fluorescent probe 1-anilinonaphthalene-8-sulfonate (ANS) is extensively utilized for examining the interaction of ligands with fatty-acid-binding proteins. The X-ray structure of FABP3 was determined in the presence of ANS and revealed the detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…For FABP3, 4 and 5, the magnitude of the entropy change on binding to ANS was hFABP5>FABP3>FABP4. These differences in thermodynamic signatures between the FABPs in this subgroup suggest ANS may bind differently across hFABP3, 4 and 5, as has been suggested by structural studies where ANS was reported to bind to hFABP3 and mFABP4 in opposite orientations (36,42).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…For FABP3, 4 and 5, the magnitude of the entropy change on binding to ANS was hFABP5>FABP3>FABP4. These differences in thermodynamic signatures between the FABPs in this subgroup suggest ANS may bind differently across hFABP3, 4 and 5, as has been suggested by structural studies where ANS was reported to bind to hFABP3 and mFABP4 in opposite orientations (36,42).…”
Section: Discussionmentioning
confidence: 78%
“…FABP1 can bind to two fatty acids (34); FABP2 binds fatty acids in a bent conformation (35) and FABP3, 4 and 5 bind to fatty acids in a U shape configuration (36)(37)(38). This conformation-specific binding appears to be associated with differences in the affinities of FABP binding to specific fatty acids (39).…”
Section: Discussionmentioning
confidence: 83%
“…The binding sites for ANS were determined in some proteins. 40,41) The elucidation of the binding site of thermolysin for ANS is the next research subject.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Purity was verified using sodium dodecyl sulfate polyacrylamide electrophoresis. Chicken eggwhite lysozyme (LZM) was purchased from Seikagaku Kogyo and used without further purification.…”
Section: Protein and Hydrogel Preparationsmentioning
confidence: 99%